Touch screens as a tool in patient care in the IBD outpatient clinic. (1st September 2016) - Larsen, Lone; Drewes, Asbjørn Mohr; Fallingborg, Jan; Jacobsen, Bent Ascanius; Jess, Tine
Abstract: Objective: We have introduced online touch screens in the waiting room for patients with ulcerative colitis (UC) or Crohn's disease (CD) for recording of symptoms before their consultation. This has made disease activity scores readily available to the physician in our newly established database, 'Gastrobio'. We wanted to validate the use of touch screens compared to paper questionnaires. Material and methods: A total of 54 patients with UC and 74 patients with CD were included in the study. The UC patients filled out the Short Health Scale (SHS) and Simple Clinical Colitis Activity Index (SSCAI). The CD patients filled out the SHS and Harvey–Bradshaw Index (HBI). Paper questionnaires and touch screen versions were used in random order and comparison between the two modalities was made by Spearman correlation test, Bland–Altman plots, and Kappa-statistics. Results: Among the 128 patients, the two SHS scores (SHS touch versus SHS paper) were found to be highly correlated (Spearman correlation; 0.92 for UC and 0.92 for CD). Also, on average, Bland–Altman plots demonstrated a difference close to zero between the two modalities. Agreement between paper version and touch screen version of SCCAI and HBI scores was also high (Kappa-statistics; 78% raw and 98% weighted for SCCAI; 65% raw and 97% weighted for HBI). Conclusions: It is feasible to introduce touch screens in the outpatient clinic and to have patients record their symptoms before the consultation. However, the study may not be representative for elderly patients.